Rancang Bangun Alat Uji Momen Inersia Massa Suatu Elemen Mesin dalam Tiga Arah Sumbu - Aji Digdoyo; Fauzhia Rahmasari; Agus Budi Djatmiko; Erma Yuniaty; Saepul Anwar (Fakultas Teknik Universitas Pancasila, 2022)
The moment of inertia of the mass is a quantity that is very much needed in designing high-speed engine parts, because it can cause a very large force and the magnitude can be thousands of times its weight. There are two ways to determine the moment of inertia, namely theoretically or testing, if using theory if the shape of machine parts is complicated, of course it is also difficult to determine the magnitude and the second way, namely by testing, it is very easy to get the price of the moment of mass inertia sought even though the shape is complicated. The moment of inertia test equipment is used to determine the value of the moment of inertia of a machine element by means of testing. This tool is also the result of its own design and engineering, which has never been developed by another party. This tool is intended to assists in the Research Development Program in the Department of Machinery, Faculty of Industrial Technology, Jayabaya University. The design of the Test Equipment is based on the Torque Moment principle where the system is considered to have mass and elasticity and from a practical and economical point of view it is very easy to implement. The results of testing the pitch direction and yaw direction with the same test object, namely the connecting rod, it turns out that the test results are Ip = 0.00298 kgm2 and Iy = 0.00304 kgm2 and for testing the direction of rotation using a mass disk of aluminum obtained Ir = 0.00125 kgm2 , the calculation results obtained Ir = 0.1271 kgm2, not too far away or it can be said that the three-axis test equipment, namely the direction of pitch, yaw and rolling can be used for testing the moment of mass inertia for machine elements.